2019
DOI: 10.1007/s11156-019-00864-x
|View full text |Cite
|
Sign up to set email alerts
|

Does idiosyncratic risk matter in IPO long-run performance?

Abstract: This paper studies how firm-level idiosyncratic risk varies over time and affects both initial public offering (IPO) and matched non-IPO firms' long-run performance. It revisits the traditional approach to compute the long-run performance by conditioning aftermarket performance on idiosyncratic risk with a generalized autoregressive conditional heteroskedasticity GARCH-M extension of the standard three-factor Fama and French (3FF) model. Our findings show a positive long-run relationship between idiosyncratic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Hence, given the high level of idiosyncratic risk that negatively affects the long-run performance of IPOs, as demonstrated by Beaulieu and Mrissa Bouden (2020), we believe that investing in funds that include IPOs could be another way to invest in IPOs while benefiting from the high initial returns during the early aftermarket stage and avoiding the IPO long-run underperformance that occurs thereafter. Moreover, indirect investment in IPOs through mutual funds is a way to avoid the risk of new issues, as the funds allow for a diversification effect, which reduces the idiosyncratic risk of stocks.…”
Section: Evidence On Ipo Performancementioning
confidence: 96%
See 1 more Smart Citation
“…Hence, given the high level of idiosyncratic risk that negatively affects the long-run performance of IPOs, as demonstrated by Beaulieu and Mrissa Bouden (2020), we believe that investing in funds that include IPOs could be another way to invest in IPOs while benefiting from the high initial returns during the early aftermarket stage and avoiding the IPO long-run underperformance that occurs thereafter. Moreover, indirect investment in IPOs through mutual funds is a way to avoid the risk of new issues, as the funds allow for a diversification effect, which reduces the idiosyncratic risk of stocks.…”
Section: Evidence On Ipo Performancementioning
confidence: 96%
“…They demonstrate that volatility varies with the complexity of the pricing problem over time. Following Campbell and Taksler (2003), who use idiosyncratic volatility to measure information asymmetry between a firm and its traders, Beaulieu and Mrissa Bouden (2020) discover that firms issuing IPOs have higher idiosyncratic risk than their non‐IPO‐issuing peers. Furthermore, they reveal that the difference in idiosyncratic risk between IPO‐issuing firms and their non‐IPO‐issuing peers is greater in the early aftermarket stage and tends to diminish by the end of the third year of IPO trading.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The idiosyncratic risk was often used to measure information asymmetry (Campbell & Taksler, 2003). Some empirical studies (Beaulieu & Bouden, 2020;Fu, 2009) found a positive relationship between volatility and idiosyncratic risk. The authors argued that investors need high premiums to hold idiosyncratic risky stocks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, they noted that more portfolios (especially in Spain and the Netherlands) contained positively idiosyncratic risks, whereas all portfolios were very damaging in the UK. Beaulieu and Bouden (2020) found that idiosyncratic risk at the firm level positively affected the IPO's return in the…”
Section: Literature Reviewmentioning
confidence: 99%